Harnessing NK cells in cancer therapies - Vivier, Eric (Henry Stewart Talks, 2025)
Innate immunity, Cancer innate immunity cycle, Innate lymphoid cells, Hallmarks of NK cell tumor immunity, Overview of NK cells, NK cell characterization, NK cell ontogeny, NK cell distribution, Antibody based NK cell engager therapeutics, Trispecific NK cell engagers, Tetraspecific NK cell engagers, Comparing NK cell engagers to T cell engagers